MEMADAMKAN API, MENGIKAT ASPIRASI: PENANGANAN KONFLIK KEAGAMAAN DI KOTA MATARAM - Akmal Salim Ruhana (Harmoni, 2014)
As a multicultural and multi-religious country, Indonesia has the potential for the eruption of ethno-religious conflict. In some cases, ethno-religious conflict has already manifested. Conflict resolution can be carried out effectively or ineffectively. This paper explores the process of conflict resolution between parties in Cakranegara, Mataram, where ethno-religious conflict between two regions identified as Sasak-Moslem and Bali-Hinduist was successfully resolved. Actors succeeded in solving the problem problem by widening the participation of stakeholders, accomodating aspirations, and strengthened the commitment to peace by a peace agreement. This qualitative research is also finds that factors such as a strong and egalitarian leadership, effective local wisdoms, and common commitment to peace supported the peace process. Factors that did not support the process included provocation by external actors and historical prejudices.